VECTOR ELECTROCARDIOGRAPHY IN THE DIAGNOSTICS OF FOCAL CHANGES IN THE MYOCARDIUM - I. Ye. Belaya; V. I. Kolomiets; G. Ye. Vislouh (Российский кардиологический журнал)
Acute coronary disease diagnostics improvement is a worldwide priority. The introduction of a promising method of study of the electromotive force of the heart with the use of information technologies, allows us to diagnose acute myocardial infarction. We have used a modern cardiodiagnostics complex MTM-SKM by Severodonetsk Scientific Production Association “Microtherm” (Ukraine).Clinical case. The presence of vectorcardiography necrobiotic processes in the left ventricle apical region, intraventricular conduction and hemodynamic overload of the atria has been revealed at the patient D., 59, with acute myocardial infarction, which was additional information that has not been registered on the ECG.Conclusion. Vector electrocardiography, allows us to investigate the periodic distribution of the electromotive force in dynamics over the entire surface of the heart, and also makes it possible to obtain detailed information about the functional state of the myocardium, specifying the depth and extent of the pathological process.